Comparison between transient and permanent congenital hypothyroidism on a thyroid function test after re-evaluation - Song Han Lee; Hyun Gyung Lee; Eun Mi Yang; Chan Jong Kim (Korean Society of Pediatric Endocrinology, 2023)
Purpose Congenital hypothyroidism (CH) is diagnosed with neonatal screening and is treated early in the neonatal period. Among these patients, transient CH (TCH) is included and requires re-evaluation. The purpose of this study was to find the best way to discontinue levothyroxine and to find trends in thyroid function tests (TFTs) after re-evaluation. Methods We retrospectively reviewed 388 patients diagnosed with CH. They were classified as permanent CH (PCH) and TCH. The total number of the PCH and TCH groups was 83 (51 boys and 32 girls). We compared clinical parameters to predict TCH and to identify the trends of TFT. Results The first thyroid-stimulating hormone (TSH) value after discontinuation and the average TSH value for 1, 2, and 3 years were all significantly higher in the PCH group (P<0.01). The first fT4 value after discontinuation and the average fT4 value for 1, 2, and 3 years were all significantly higher in the TCH group (P<0.01). The optimal cutoff value on the receiver operating characteristic curve for PCH prediction with an average of 3 years of TSH was greater than 9.05 μIU/mL, which was predicted with a sensitivity of 100% and a specificity of 100%. Conclusions When the TSH value ranges from 10 μIU/mL to 20 μIU/mL, clinicians can discontinue levothyroxine if the next result is around 10 μIU/mL or shows a decreasing trend.